Solar heat for industrial processes : technology brief (International Energy Agency ; International Renewable Energy Agency, 2015)
This IRENA/IEA-ETSAP Technology Brief provides technical background, analyses the potential and barriers for market growth, and offers insights for policy makers on this key renewable energy technology. Solar thermal systems (STS) can fulfill a substantial amount of heat demand in industrial and agricultural food processes within any given country and irrespective of the geographical location. In developed economies, solar thermal can provide technically about half of this energy consumption by supplying hot water and steam in a temperature range of up to 400°C. In developing countries, especially in those where agriculture, the textile, brick and food processing industries are important sub-sectors, solar thermal energy can provide hot air and hot water needed for curing, drying, dyeing, washing, boiling, pasteurisation and sterilisation. Despite the technical potential, as well as the potential economic benefits of using solar heat in industry, actual deployment levels remain quite low. STS uptake requires policy-making to create the right conditions. High upfront costs are a barrier to STS adoption, particularly for small or mid-sized companies.